KERUSAKAN TIPE EKOSISTEM KARST DAN PENGARUHNYA TERHADAP PERUBAHAN IKLIM (SUATU PENDEKATAN TEORI) - Benteng H Sihombing (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2011)
KERUSAKAN TIPE EKOSISTEM KARST DAN PENGARUHNYA TERHADAP PERUBAHAN IKLIM (SUATU PENDEKATAN TEORI) The Damage of Karst Ecosystem and Its Impact on The Climate Change (a theoretical approach)Benteng. H SihombingFakultas Kehutanan, Universitas MulawarmanSamarinda ABSTRACTKarst ecosystem poses high economic potency however its attention was lack due to to date only pay attentions merely on mineral resource potency, and its conservation measure only focus to some extent on cave. Mean while, karst area owns wider protective function, such as water conservation, state revenue from tourism, mining, bird nest, even it closely relates to the national security issue and state intelligence. Pay an attention on karst ecosystem that covers biotic potency and mineral energy exploration is tought to be far from seriousness meanwhile its tension on this ecosystem tends to be larger, even already comes to the stage of ecology endanger. In relation to the global temperature rise that leads to the climate change, natural karst ecosystem seems pay a big role in reducing carbondioxide through karstifikasi process. Therefore, the karst ecosystem conservation is an urgent agenda.Key words : Karst, Ecosystem, Climate change.